Mechanisms of disorders of ischemic liver damage and ways of their correction using a new amino acid mixture based on sodium succinate and mannitol (Genius Repository, 2023)
During the reproduction of experimental toxic hepatitis by administering heliotrine, it was found that the HIF-1 content averaged 0.101667±0.0022 ng/l. In blood plasma, the average HIF-1 values were 0.2136±0.0066 ng/l. After treatment in group I, HIF-1α indices were 0.317±0.022 (p